Streptomyces RNases – Function and impact on antibiotic synthesis - Jones, George H. (Frontiers in Microbiology, 2023)
Streptomyces are soil dwelling bacterial that are notable for their ability to sporulate and to produce antibiotics and other secondary metabolites. Antibiotic biosynthesis is controlled by a variety of complex regulatory networks, involving activators, repressors, signaling molecules and other regulatory elements. One group of enzymes that affects antibiotic synthesis in Streptomyces is the ribonucleases. In this review, the function of five ribonucleases, RNase E, RNase J, polynucleotide phosphorylase, RNase III and oligoribonuclease, and their impact on antibiotic production will be discussed. Mechanisms for the effects of RNase action on antibiotic synthesis is proposed.